Diagnóstico etiológico de la sordera infantil: Recomendaciones CODEPEH 2015 - Núñez Batalla, Faustino; Jáudenes Casaubón, Carmen; Sequí Canet, José Miguel; Vivanco Allende, Ana; Zubicaray Ugarteche, José; Cabanillas Farpón, Rubén (Revista Española de Discapacidad, 2016)
Núñez, F. et al. (2016): “Diagnóstico etiológico de la sordera infantil: Recomendaciones CODEPEH 2015”, Revista Española de Discapacidad, 4 (1): 193-218.